2007
DOI: 10.5551/jat.14.65
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Contrast Medium Detects Increased Permeability of Rat Injured Carotid Arteries in Magnetic Resonance T2 Mapping Imaging

Abstract: Aim: Aim of this study was to directly detect increased permeability of vascular lesions by magnetic resonance imaging. Methods: A novel contrast medium with a mean hydrodynamic diameter of 100 nm was prepared from monodispersed iron colloids incorporated into micelles of block copolymers composed of polyethylene glycol and polyamino acid. T2 mapping was applied to differentiate the minimal shortening of T2 relaxation time in balloon-injured rat carotid arteries. Results: The novel contrast medium accumulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Polymeric micelles are being developed as total delivery systems integrating multifunctionality to improve their efficacy. Although this review focuses on anti-cancer drugs and pDNA as deliverable materials, we have also developed DDS for other therapeutic materials such as proteins (Jaturanpinyo et al 2004;Yuan et al 2005;Kawamura et al 2007), siRNA (Itaka et al 2004;Kakizawa et al 2006;Matsumoto et al 2009), imaging agents for diagnosis (Imai et al 2007;Kumagai et al 2007) and photosensitizers for photodynamic therapy (Ideta et al 2005;Jang et al 2005Jang et al , 2006Jang et al , 2007 or co-delivery with pDNA for photochemical gene delivery (Nishiyama et al 2005(Nishiyama et al , 2007Arnida et al 2006). The development of polymeric micelles with smart functions such as environment sensitivity and tissue selectivity may enhance the desired activity of potent bioactive compounds, facilitating their clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Polymeric micelles are being developed as total delivery systems integrating multifunctionality to improve their efficacy. Although this review focuses on anti-cancer drugs and pDNA as deliverable materials, we have also developed DDS for other therapeutic materials such as proteins (Jaturanpinyo et al 2004;Yuan et al 2005;Kawamura et al 2007), siRNA (Itaka et al 2004;Kakizawa et al 2006;Matsumoto et al 2009), imaging agents for diagnosis (Imai et al 2007;Kumagai et al 2007) and photosensitizers for photodynamic therapy (Ideta et al 2005;Jang et al 2005Jang et al , 2006Jang et al , 2007 or co-delivery with pDNA for photochemical gene delivery (Nishiyama et al 2005(Nishiyama et al , 2007Arnida et al 2006). The development of polymeric micelles with smart functions such as environment sensitivity and tissue selectivity may enhance the desired activity of potent bioactive compounds, facilitating their clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…For example Imai et al [34] showed increased accumulation of a novel iron oxide contrast medium in the injured carotid arteries of rats by T2 mapping. Chaabane et al [35] and Alsaid et al [36] evaluated plaque permeability in a murine model of atherosclerosis using novel blood pool agents.…”
Section: Contrast-enhanced Mri Approaches For Characterization Of Thementioning
confidence: 98%